إيالة الجزائر خلال القرن الثامن عشر من خلال كتاب الرحالةالإنجليزي توماس شو (1720-1732م) - طايع رشيدة; لبادي آية (My University, 2024)
Abstract The memo "Dr. Shaw's Journey" details Thomas Shaw's voyage to Algeria in the 18th century, highlighting the social, cultural, and political conditions in the Regency of Algiers under Ottoman rule. The memo aims to provide an accurate description of various aspects of life in Algeria from a European perspective, discussing the impact of Ottoman governance on the local population. Shaw's observations on education, arts, and sciences reveal a decline in these areas due to a focus on commercial and financial aspects. He also criticizes the health conditions and the limited medical knowledge among the populace. The memo also covers Algeria's strategic importance in the Mediterranean and its economic status as a significant center for trade and culture. The study employs a scientific and methodical approach in map drawing and geography, along with precise comparisons between various sources. Shaw's journey reflects his role as an explorer and scholar seeking to understand and analyze his -------------------------------------------------- ملخص باللغة العربية تتناول مذكرة "رحلة دكتور شو" رحلة توماس شو إلى الجزائر خلال القرن الثامن عشر، حيث تسلط الضوء على الأوضاع الاجتماعية، الثقافية، والسياسية في أيالة الجزائر تحت الحكم العثماني. تهدف المذكرة إلى تقديم وصف دقيق لمختلف جوانب الحياة في الجزائر من منظور أوروبي، وتناقش تأثير الحكم العثماني على السكان المحليين. يُبرز شو في رحلته مشاهداته حول التعليم والفنون والعلوم، مشيرًا إلى تدهور هذه المجالات بسبب التركيز على الجوانب التجارية والمالية. كما ينتقد شو الأوضاع الصحية ومحدودية المعرفة الطبية بين السكان. تغطي المذكرة أيضًا أهمية الجزائر الاستراتيجية في البحر الأبيض المتوسط ومكانتها الاقتصادية، حيث كانت مركزًا هامًا للتجارة والثقافة. تعتمد الدراسة على منهج علمي ومنهجي في وصف الخرائط والجغرافيا، بالإضافة إلى مقارنات دقيقة بين مصادر متعددة. المذكرة تعكس رؤية شو كمستكشف وعالم يسعى لفهم وتحليل البيئة المحيطة به بشكل شامل ومفصل --------------------------------------- Résumé Le mémo « Le voyage du Dr Shaw » détaille le voyage de Thomas Shaw en Algérie au XVIIIe siècle, soulignant les conditions sociales, culturelles et politiques de la régence d'Alger sous la domination ottomane. Le mémo vise à fournir une description précise des différents aspects de la vie en Algérie d'un point de vue européen, en discutant de l'impact de la gouvernance ottomane sur la population locale. Les observations de Shaw sur l'éducation, les arts et les sciences révèlent un déclin dans ces domaines en raison de l'accent mis sur les aspects commerciaux et financiers. Il critique également les conditions de santé et les connaissances médicales limitées de la population. Le mémo couvre également l'importance stratégique de l'Algérie en Méditerranée et son statut économique en tant que centre important pour le commerce et la culture. L'étude utilise une approche scientifique et méthodique en dessin de carte et en géographie, ainsi que des comparaisons précises entre diverses sources. Le parcours de Shaw reflète son rôle d'explorateur et d'érudit cherchant à comprendre et à analyser ses
Keywords: إيالة الجزائر، رحلة الدكتور شو، التنظيم السياسي والعسكري، الحياة الاجتماعية